Dialogic reading in the rehabilitation of Children with Hearing Loss and the "Born to Read" Project: A pilot study. Issue 5 (5th July 2018) - Continisio, Grazia Isabella; Mattiello, Amalia; Toscano, Silvia; Continisio, Paola; Paternoster, Mariano; Guarino, Alfredo; Cuomo, Francesca Maria; Cristiani, Tiziana; Manetti, Stefania; Giannattasio, Antonietta; Marciano, Elio
Abstract : The "born to read" initiative entails a dialogic reading to children in poor socio‐economical conditions aimed at fostering cognitive and relational skills. Reading is professionally delivered by experts to promote psycho‐social development of children and their parents. In this study the project was extended to include children positive at early screening for hearing impairment. A total of 26 children were included and 14 parents were taught to read aloud and emphatically. Reading session were delivered for at least 10 minutes at least 3 times/week, usually at bedtime, for one year. The Griffiths scale were applied to explore the expressive and receptive language skills (Scale C) and eye and hand coordination (Scale D), as measures of linguistic and neurocognitive skills. Program sustainability and reactions by the parents were also investigated. All 14 families successfully received the training, becoming capable of reading aloud and emphatically and provided reading sessions for the entire duration of the study. Children receiving the intervention performed slightly better than controls and those who were exposed to increased number of sessions, performed even better although the differences with controls were not significant. Parents enjoyed reading to their children. They expressed satisfaction and gratitude for being able to play an active and productive role in children rehabilitation. The results of this pilot study suggest that the born to read initiative may be considered in adjunct to medical and psychological interventions to enhance the benefits of early screening of hearing function.